2020
DOI: 10.3390/su12125146
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior towards Regional Eco-Labels in Slovakia

Abstract: Slovakia, as part of the European Union, participates in all forms of regional development and sustainability. A transparent form of regional development and sustainability is regional labeling, which has a 10-year tradition. Our regions represent excellent potential for the development of domestic products. Acceptance of essential requirements for regional products (domestic raw materials, manual work share, respect for the environment) opens up opportunities for the labor market, promotes tourism, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…On the other hand, consumers who attach less importance to ecolabels are young people with basic/elementary studies. These results are consistent with the findings of several previous studies (Jadudov a et al, 2020;Rice, 2006;Teisl et al, 2008).…”
Section: Conclusion and Entrepreneurial Implicationssupporting
confidence: 94%
“…On the other hand, consumers who attach less importance to ecolabels are young people with basic/elementary studies. These results are consistent with the findings of several previous studies (Jadudov a et al, 2020;Rice, 2006;Teisl et al, 2008).…”
Section: Conclusion and Entrepreneurial Implicationssupporting
confidence: 94%
“…There is a tendency in food-related research on labeling in recent years to be focused on sustainability labeling and certification [33]. It has been demonstrated that sustainabilityoriented labels receive greater evaluations than non-sustainability ones with customers who are concerned with social desirability and that sustainability claims can improve perceived flavor of the product, but sustainability claims cannot replace the importance of sensory attributes such as flavor in hedonic products [34,35].…”
Section: Sustainability Labeling and Packaging In The Food And Beverage Industrymentioning
confidence: 99%
“…As a result, they uplifted their positioning, increased their sales, established their sustainability platform, and situated themselves as good corporate citizens [64]. Eco-labeling is a marketing tool that can be used to promote the awareness of sustainable consumerism [14,22].…”
Section: Awarenessmentioning
confidence: 99%
“…Consequently, third-party organizations, as well as producers of green products, have come into action to standardize and certify operational processes through eco-labeling their merchandise. In turn, multiple eco-labels have emerged in the market, creating diversity in the sustainability standards and their corresponding stamps such as Fairtrade and Rainforest Alliance stamps [14,15].…”
Section: Introductionmentioning
confidence: 99%